Penyuluhan Metode Pembelajaran Matematika Menyenangkan di SD Negeri 01 Karet Kuningan - Evayenny Evayenny; Nanda Lega Jaya Putra; Syamzah Ayuningrum (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2021)
Basic education is undertaken when students are in a period of great potential to be influenced, both positively and negatively. the situation that occurred in SD Negeri Karet Kuningan 01 Pagi, students still have difficulty understanding abstract mathematics material, the lack of teacher knowledge about effective learning methods causes less innovative learning. This phenomenon shows that the teacher's need for a good understanding of mathematics learning methods is an absolute must. The problem that occurred at SD Negeri Karet Kuningan 01 Pagi is the background for the service being carried out. This activity aims to provide knowledge and determine appropriate learning methods for learning mathematics in elementary schools. This PKM is carried out in the form of training, the presentation material in this service activity, namely: (1) Concept of learning methods in accordance with the characteristics of Mathematics subjects (2) Preparation of lesson plans (RPP) with appropriate learning methods (3) Simulation of implementing methods cooperative learning in learning, and (4) assessment of learning using learning methods. Conclusion of this service. Participants are able to carry out learning using the mathematics learning method, the enthusiasm of the participants is high in participating in this training because the material offered is very suitable for their needs as elementary school teachers. Appropriate learning methods can improve the quality of learning, as well as stimulate the ability to work together and a sense of responsibility for elementary students.